An Analysis of Tourism Facilities and Services Influencing Tourist Satisfaction in Indonesia Tourism - Griselda Salsabila, Yori (Lafadz Jaya Publisher, 2024)
This research reflects the level of satisfaction among customers within Indonesia's tourism sector, especially in Bali, a globally renowned island destination. Key elements affecting the satisfaction of tourists in Indonesia include tourism facilities, tourist information, and tourism infrastructure. The aim of this research is to recognize and gather empirical evidence to draw conclusions regarding the satisfaction of foreign tourists. The research method is a descriptive quantitative approach with a sample size of 250 individuals. Data is collected through observation and a questionnaire survey. Analysis involves multiple linear regression analysis, hypothesis testing, and the determination coefficient method using SPSS 26. The findings indicate that tourism facilities, tourist information, and tourism infrastructure collectively contribute to a 90.4% influence on the satisfaction of foreign tourists. A segment of the research shows tourism facilities have no influence on tourist satisfaction and the significant positive influence of tourist information and tourism infrastructure on tourist satisfaction. Hence, it is essential to enhance and maintain these facilities.